Encapsulated propionic acid as a silage additive. Issue 1 (2nd January 2016) - Rutenberg, Roi; Granit, Rina; Chen, Yaira; Poverenov, Elena; Weinberg, Zwi G.
ABSTRACT: Various propionic acid (PA) based additives are used to successfully inhibit fungi in silages. These additives are all introduced directly, and an encapsulated formulation of PA has not yet been examined for its antifungal abilities. The current study's objective was to test the possibility of using encapsulated PA as a silage additive. Carboxymethylcellulose (CMC)-based films (film A) and CMC/β-cyclodextrin-based films (film B) were used as biodegradable matrix platforms for encapsulated PA delivery and tested on whole-crop wheat and corn silages. Films were added as a mixture combined with the silage or divided at the top and bottom of the bulk silage system. A Lactobacillus plantarum inoculation procedure was also examined for its effects. In the wheat ensiling experiment, film B resulted in the highest PA concentrations after 2 weeks (1.4% and 1.1% in dry matter for the mixed and divided films, respectively). Mixed film A also produced high levels of PA after 2 weeks. Lactic acid (LA) concentrations peaked after 2 weeks and the highest final concentrations were obtained in the L . plantarum treatment. The highest PA concentrations in the corn silages were measured at the end of the experiment. Film B tended to result in slightly higher PA concentrations than film A. LA concentrations peaked after 2 weeks and the highest final content was obtained with film B. Overall, this study demonstrates that addition of encapsulated PA to biodegradable CMC films may provide an advanced safe approach for retaining silage quality and wastage reduction.